Desempenho de híbrido de girassol em resposta ao vigor das sementes, população de plantas e desuniformidade de semeadura, no outono de 2009 em Uberlândia-MG - Brunes, Rélia Rodrigues (2010)
In the sunflower cultivation seedlings dominated probably because of nonuniformity between seeds from the same portion is a common occurrence. This variation results from a natural gradient of seed maturation in the capitulum, which has demanded a rigorous processing to reduce variation. Although the relationship between nonuniform emergence and productivity is already known, there is a lack of scientific findings on it. This study aimed to evaluate the performance of hybrid sunflower in response to seed vigor, plant density, and uniformity of sowing during 2009 autumn in Uberlândia, Brazil, with a focus on the behavior of individual plants and the resulting overall performance of communities. Two experiments were carried out at Uberlândia s Federal University s Glória Experimental Farm. The first trial was a randomized block design with four replications. Treatments consisted of seven combinations of high and low vigor seed s distribution along the seeding line, which corresponded to the following ratios of plants sprung from seeds of high vigor in the community: 1,0 (1A:1A); 0,75 (3A:1B); 0,67 (2A:1B); 0,50 (1A:1B); 0,33 (1A:2B); 0,25 (1A:3B); 0,0 (1B:1B). The second trial was a randomized block design with a split plot arrangement with five replications. Four populations (35,000, 40,000, 45,000 and 50,000 plants ha 1) were evaluated; and in the split plots it was evaluated the sowing uniformity through the variation in the sowing date, being: 1) uniform sowing (0 0 0 0); 2) interspersed sowing seeds seven days after the first sowing (0 7 0 7); 3) interspersed sowing fourteen days after the first sowing (0 14 0 14); 4) sowing seven days and fourteen days after the first sowing (0 7 14 0). We evaluated the emergence measures, seedlings survival 60 days after the first sowing and in the harvest, capitulum diameter and height, moisture, and productivity. We conclude that: a) seed vigor combinations did not affect capitulum diameter and height, plant survival, moisture, and productivity of sunflower communities; b) the increase in the proportion of high vigor seeds increased linearly the productivity of individual plants sprung from high vigor seeds within communities, although they did not show a dominant behavior over low vigor adjacent plants in the sowing line; c) emergence, survival 60 days after sowing and in the harvest (community), and capitulum diameter (individual performance of uniform sowing plants) reduced with the increase of plant population; d) in the analysis of individual plants according to sowing nonuniformity, uniform sowing plants had a superior performance as to capitulum diameter and productivity, while there was no differences in productivity due to population and sowing nonuniformity in the community.